1997
DOI: 10.1007/s004210050296
|View full text |Cite
|
Sign up to set email alerts
|

Positive end expiratory pressure as a method for preventing acute mountain sickness

Abstract: In order to study the use of positive end expiratory pressure (PEEP) to prevent acute mountain sickness (AMS), 22 subjects were exposed randomly to 8-h hypobaric hypoxia in a hypobaric chamber (4500 m, 589 hPa, 22 degrees C) once being administered 5-cm H2O PEEP and once without. The prevention of AMS by PEEP was evaluated by scoring AMS according to the Lake Louise system (self-report questionnaire and clinical assessment) throughout the experiment with O2 saturation (SO2) and heart rate measurements being ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…This observation may be related to an increase in alveolar ventilation, as reported by Savourey et al (7) in their study using the same system under laboratory conditions. The absence of a significant change in heart rate and in arterial blood pressure attests that the PEEP-5 system does not modify the cardiac variables, as also reported by Savourey et al (4,7,8). In the same way, the PEEP-5 system in our experiment did not affect microhematocrit after the ascent of Mount Blanc.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This observation may be related to an increase in alveolar ventilation, as reported by Savourey et al (7) in their study using the same system under laboratory conditions. The absence of a significant change in heart rate and in arterial blood pressure attests that the PEEP-5 system does not modify the cardiac variables, as also reported by Savourey et al (4,7,8). In the same way, the PEEP-5 system in our experiment did not affect microhematocrit after the ascent of Mount Blanc.…”
Section: Discussionsupporting
confidence: 61%
“…The PEEP prototype has been described earlier (4), and it was calibrated before each experiment. Briefly, it consisted of a bi-directional valve (patent 96402315-4-2309 Etat français) that applied a PEEP of 5-cm H 2 O and was attached to a Hans Rudolf face mask with a low dead space (Hans Rudolph Inc, Kansas City, MI, USA).…”
Section: Postitive End-expiratory Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…The findings from this research are in agreement with previous findings that CPAP, PEEP, Auto-PEEP/ pursed lip breathing, and EPAP used at high altitude, rapidly increases the oxygen saturation (Schoene et al, 1985;Savourey et al, 1998;Davis et al, 1999;Launay et al, 2004;Tannheimer et al, 2009;Agostoni et al, 2010). The low number of subjects limits the robustness of the findings but it is clear that CPAP provides potential for treating this common disorder in an area where treatment availability is limited.…”
Section: Discussionsupporting
confidence: 81%
“…Other investigations into positive airway pressure at high altitude have found that, in awake subjects, positive end expiratory pressure (PEEP) applied via face mask increased Spo 2 and decreased AMS symptoms (Schoene et al, 1985) or decreased AMS but did not significantly improve Spo 2 (Savourey et al, 1998;Launay et al, 2004). Continuous positive airway pressure (CPAP) was used after ascent to 3205 m on Mount Cook in New Zealand; it improved Spo 2 and reduced symptoms of high altitude pulmonary edema (Davis et al, 1999).…”
Section: High Altitude Medicine and Biologymentioning
confidence: 99%